Assessing early childhood teachers' perceptions of the role of the integrative curriculum in promoting children's learning experiences - AlAli, Rommel Mahmoud; Al-Barakat, Ali Ahmad (Edelweiss Applied Science and Technology, 2024)
This study aims to assess early childhood teachers' perceptions of the role of an integrative curriculum in enhancing children's learning experiences, focusing on its impact on understanding academic relationships and developing social and personal skills. The study used a quantitative design, using a carefully structured and validated questionnaire to gather data from a randomly selected sample of 773 early childhood teachers in northern Jordan. The methodology ensured the reliability and validity of the instrument, strengthening the credibility of the results. The results indicated that all questionnaire items achieved high average scores, indicating a strong consensus among teachers regarding the positive effects of an integrative curriculum. Teachers affirmed that such a curriculum deepens children's understanding of connections between academic subjects and contributes to the development of their social and personal competencies. Furthermore, activities related to children's daily lives were found to significantly improve motivation, as children engage more actively when they perceive real-life applications of their learning. In conclusion, the study highlights the critical role of an integrative curriculum in early education, emphasizing its contribution to both academic and personal development. The research recommends further development of curricula that incorporate activities reflecting children's everyday lives, alongside the implementation of specialized teacher training programs to improve their ability to design and deliver interactive learning experiences. These practical implications emphasize the significance of integrating real-world connections into early childhood education, helping prepare children to adapt to modern societal challenges.